Dampak Kesadaran Wajib Pajak dan Kualitas Layanan Pegawai Pajak Terhadap Kepatuhan Wajib Pajak Badan yang Dimoderasi oleh E-System - Putri Mirna Nadila; Surna Lastri; Tarmizi Gadeng (AKUNTANSI 45, 2025)
This study aims to investigate the effect of corporate taxpayer awareness and the quality of tax officer services on corporate taxpayer compliance moderated by the E-System at the Tax Service, Counseling, and Consultation Office (KP2KP) of Sabang City in 2023. The research sample was determined using a random sampling method, with a sample size of 100 corporate taxpayers. Data analysis was conducted using Moderated Regression Analysis with E-Views13. The results show that corporate taxpayer awareness has a significant effect on corporate taxpayer compliance. In addition, the quality of tax officer services also has a significant effect on corporate taxpayer compliance. However, the E-System does not have a direct effect on corporate taxpayer compliance. Nevertheless, the E-System is proven to moderate the effect of corporate taxpayer awareness on corporate taxpayer compliance. Conversely, the E-System is unable to moderate the effect of tax officer service quality on corporate taxpayer compliance at the KP2KP of Sabang City. This study provides insight into the effectiveness of the E-System in improving taxpayer compliance.